Knowledge and utilization of technology-based interventions for substance use disorders: an exploratory study among health professionals in the European Union - Quaglio, Gianluca; Pirona, Alessandro; Esposito, Giovanni; Karapiperis, Theodoros; Brand, Helmut; Dom, Geert; Bertinato, Luigi; Montanari, Linda; Kiefer, Falk; Carrà, Giuseppe (Drugs, 2018)
Background: Little is known about the knowledge and use of technology-based interventions (TBIs) by health personnel working in the addiction field across Europe.Methods: An online questionnaire was designed using SurveyMonkey® in order to determine the level of knowledge, use and perceived efficacy of TBIs in substance use disorders (SUDs), among health professionals across six EU Member States: Germany, Italy, UK, France, Poland and the Netherlands. The survey was sent to a convenience sample of 1200 addiction experts.Results: Surveyed participants (311, response rate 26%), had a mean professional addiction experience of 17 years; 23% stated to have good knowledge of TBIs, while 12% use them in their clinical practice. Forty-six percent consider TBIs useful in the treatment of addiction, and 44% foresee a significant increase of them in the future. TBIs were considered important for people facing barriers to accessing treatment (63%) and for providing support outside the formal care settings (60%). Lack of technical support (48%), poor infrastructure and equipment (42%), and lack of digital literacy among health workers (38%) were identified as the main obstacles in the diffusion of TBIs.Conclusions: Knowledge and utilisation of TBIs among health workers in drug addiction field is low. Nevertheless, TBIs are perceived as a possible means of facilitation in providing access to treatment, and as therapeutic tools which will become more important in the future. The need to improve training policies, awareness and attitudes towards TBIs among EU health professionals, working in the field of addiction is paramount.